Natural Variation in Physiological Responses of Tunisian Hedysarum carnosum Under Iron Deficiency - Ben Abdallah, Heithem; Mai, Hans Jörg; Slatni, Tarek; Fink-Straube, Claudia; Abdelly, Chedly; Bauer, Petra (Frontiers in Plant Science, 2018)
Iron (Fe) is an essential element for plant growth and development. The cultivation of leguminous plants has generated strong interest because of their growth even on poor soils. Calcareous and saline soils with poor mineral availability are wide-spread in Tunisia. In an attempt to select better forage crops adapted to Tunisian soils, we characterized Fe deficiency responses of three different isolates of Hedysarum carnosum, an endemic Tunisian extremophile species growing in native stands in salt and calcareous soil conditions. H. carnosum is a non-model crop. The three isolates, named according to their habitats Karkar, Thelja and Douiret, differed in the expression of Fe deficiency symptoms like morphology, leaf chlorosis with compromised leaf chlorophyll content and photosynthetic capacity and leaf metal contents. Across these parameters Thelja was found to be tolerant, while Karkar and Douiret were susceptible to Fe deficiency stress. The three physiological and molecular indicators of the iron deficiency response in roots, Fe reductase activity, growth medium acidification and induction of the IRON-REGULATED TRANSPORTER1 homolog, indicated that all lines responded to -Fe, however, varied in the strength of the different responses. We conclude that the individual lines have distinct adaptation capacities to react to iron deficiency, presumably involving mechanisms of whole-plant iron homeostasis and internal metal distribution. The Fe deficiency tolerance of Thelja might be linked with adaptation to its natural habitat on calcareous soil.